A rare case of traumatic penetrating chest injury with hemopneumothorax (Indian Journal of Case Reports, 2018)
Thoracic trauma contributes to one-quarter of trauma deaths. Traumatic hemothorax is commonly associated with organ damage, such as rib fracture, lung injury, and diaphragm rupture and usually occurs immediately after trauma. Here, we report the case of an 18-year-old male patient of a road traffic accident. He was admitted with an open chest wound and fractured ribs with exposed heart, left hemidiaphragm, left lung, and left thoracic cavity. He had fractured lower ribs with the contusion of intercostal and pectoral muscles. The wound was explored proper toileting of the wound, and the left chest cavity was done. A tear in the left lung was repaired, ribs were positioned, and the chest wall was reconstructed without using any prosthesis. In the post-operative period, the patient developed partial flap necrosis and so he was referred to plastic surgery where debridement and pedicled latissimus dorsi flap were applied. The patient got discharge after about 1 month of the post-operative period.